JESSICA DAN KONSTRUKSI MEDIA ONLINE (FRAMING BERITA PEMBACAAN VONIS JESSICA KUMALA WONGSO DI DETIK.COM DAN VIVA.CO.ID PERIODE 27 OKTOBER 2016) - Indah Suryawati (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
This reseacrh are conducted to gain, first, knowing that Detik.com and Vica.co.id relating to the figure of Jessica Kumala Wongso in the news of her Accusation dated on October 27, 2016. Second, knowing the side of being forwarded or hided from the figure of Jessica in reporting the Accusation of her in both media of Detik.com and Viva.co.id.  The  third,  understanding  the  analysis  of  Robert  N.  Entman‟s  Framing...  for  the  news  of  its accusation in both media. This available research metode to be used is an analysis of Framing from Robert N. Entman. There are two analysis to be done. First, by using the approach of issues selection and aspect selection. Second, by using the approach of four elements;  define problem, diagnose causes, make moral judgement, and treatment recommendation. This research result shows up that Detik.com able to transfer the negative judgment in constructing who actually Jessica is. However, Detik.com is more reflecting Jessica as the murder of Wayan Mirna. Thus, the statements of the sources taken by Detik.com have also strengthen the negative constuction of her. Meanwhile, Viva.co.id gives the neutral judgement in reflecting who Jessica is. In one side, this media has also turn up Jessica as the pogrom murder. But in another side, the media which is Viva.co.id feels that this case is  weak.  It  can  be  seen  through  the  statements  of  the  news  sources  from  the  experts  that  taken  by  it.  As  the result, those expert statements are lighten the accusation of Jessica.  Keywords:  Construction, Framing, News for the Accusation of Jessica